Current research: Training for strength, power, and speed - Haff, G. G. (Strength and Conditioning Journal, 2012)
This research brief covers concurrent strength and endurance training in elite soccer players, the effect of hypertrophy training protocols with maximal loading on neural drive, the effect of cluster sets on power in jump squats, and the effect of age on repeated-sprint ability in youth soccer players.